La théorie économique des choix de carrière : une interprétation et une vérification empirique - Lemelin, Clément; Otis, Jean-Claude (L'Actualité économique, 1978)
In their choice of a field of study, students are assumed by the "neoclassical" theory to be rational, well informed, flexible, and to react to changes in monetary variables. Data from a survey are used to show that students are economic men and women only in a weak sense: 1) they appear to be more interested in job availabilities and other job characteristics than in earnings associated with a particular field of study; 2) if their information can be said to be good with respect to forgone earnings and starting earnings of their chosen occupation such is not the case with respect to future earnings; 3) however, their expected rates of return on their studies seem plausible and show all the usual properties of rates of return derived from more conventional computations.